Desired Educational Ecosystem in the Fast-Growing Educational Institutes in India - Vedhathiri, Thanikachalam (Journal of Engineering Education Transformations, 2019)
In the 21st century, the Indian economy has to grow faster than its rivals. It depends on the production of knowledge and human capitals by the state technical universities, autonomous institutes, and deemed universities. Hence, the high- performing engineering faculty members have to be assisted and supported by an appropriate academic ecosystem as other global research universities perfected by them. Well- developed engineering universities in China, Japan, Korea and Singapore have introduced many administrative processes to support their key performing faculties to reach excellence and global leadership. This demands most appropriate and continuously supporting academic system too. A snap study has been undertaken to identify the most desirable academic ecosystem in the well-performing engineering institutes in the southern states of India. 131 Senior Faculty members at Assistant, Associate, and Professors’ cadre have been selected to form a Quality Circle to identify the desired academic ecosystem. These participants attended the workshops on Higher Education Administration, Leadership Development and Institutional Development. The significant outcomes are as follows: 1. Unbiased Faculty Recruitment System which focuses on the Excellence, 2. Skill Focused Induction and In-House Training Processes, 3. Cognitive and Higher Order Training and Development Processes as per Emerging Needs, 4. Appreciative Performance Inquiry, 5. Counselling, Coaching and Mentoring the Emerging High Performers, 6. Digital-based Instructional Packages Production Center, 7. Sabbatical Leave to Undergo Faculty Development Programs to meet the Emerging needs under IDAs, 8. Implementation of Appropriate Reward System like new pay scales as approved by AICTE, 9. Sanction of Funds to Participate in the International Conferences as per the Rules, Norms, and Standards, and 10. Approval for accepting the International Invitations to participate in the Conferences and Summits without any grants. All these would enhance the academic ecosystem.